Evaluating and modelling of thermodynamic and environmental parameters of a gas turbine engine and its components - Aygun, Hakan; Caliskan, Hakan (Elsevier Sci Ltd, 2022)
Nowadays, aero-engines have been opted more due to their important benefits for powering unmanned aerial vehicles or producing electricity or pneumatic powers for aircraft engines. In this study, a small gas turbine engine (S-GTE) used in aviation applications was dealt with using thermodynamic and environmental methods at ten different power settings (PSs) as well as different design variables involving turbine inlet temperature (TIT) ranging 1350 K and 1550 K and pressure ratio of compressor ranging 10 and 16. Thus, both effects of design variables and power settings on thermo-environmental metrics were investigated under different cases. Addi-tionally, several parameters of the engine were modelled according to power settings which the engine operate. When considering performance findings, specific fuel consumption increases from 0.3262 kg/kWh to 1.2341 kg/kWh as shaft power decreases from 415 kW to 41.6 kW. According to thermodynamics computations, exergy efficiency of the combustor diminishes from 83.52% to 74.92% at baseline. Moreover, the higher TIT leads this metric to increase from 83.52% to 87.17%, whereas effect of CPR is not observed as important as the impact off TIT. However, exergy efficiency of the whole engine changes from 24.15% to 6.38% due to decrement in the PS. Moreover, the higher TIT and CPR of the engine favorably affect this metric. On the other hand, enviroeconomic cost factor (ECF) of the engine drops from 39.65 billion Euro/year to 14.98 billion Euro/year, but environmental effect factor increases 2.62 to 9.29 due to decreasing PS. Lastly, there is non-linear relationship between exergy efficiency and power setting, whereas enviroeconomic factor of the engine linearly changes with PSs. Namely, exergetic model is obtained with high accuracy as R(2 )of 0.995 at three-degree function while enviroeconomic cost factor model is achieved with high correctness as R-2 of 0.9972 at first-degree function. These results show that modelling of thermodynamic metrics helps in understanding how extent these indicators pertinent to the engine are affected from power settings. Thus, optimum power setting without penalty on the engine perfor-mance could be discovered.
Keywords: Exergetic modelling; Gas turbine engine; Enviro-economic; Design variables; Sustainability; Environmental assessment